Multidisciplinary analysis of a forbidden fishery: case study of the fishery of goliath groper Epinephelus itajara (Lichtenstein, 1822) in Pará coast, oriental Amazon (Research, Society and Development, 2020)
The goliath grouper is an endangered species that has had a moratorium instituted since 2002, valid until 2023. However, catches are common in many Amazonian ports and, in this scenario, the objective of this study was to obtain information from fishermen in Pará about the efficiency and applicability of legislation current, in the State of Pará and through a multidisciplinary analysis (RAPFISH), characterize these fisheries in their economic, social, ecological, technological and management aspects. The data were obtained through interviews with semi-structured forms applied to fishermen, masters and vessels owners in the period from August 2016 to March 2017, in the municipalities of Bragança, Curuçá and Viseu using the “snowball” technique. The data were tabulated and analyzed in Microsoft Office Excel spreadsheets. The total of 60 interviews was conceived to equalize the number of fishermen in each location studied (20 per municipality). The use of the RAPFISH methodology allowed to characterize and evaluate the fishing of Epinephelus itajara, under five dimensions and in terms of sustainability. However, in none of them was it possible to verify any indications of maintenance of this fishery. The goliath grouper fishing on the coast of Pará is quite common, where inspections, seizures and punishments are rare. In this sense, it is reiterated the requirement for more expressive monitoring in order to minimize the deleterious effects of this practice on natural populations.